2021
DOI: 10.1186/s12864-021-08186-w
|View full text |Cite|
|
Sign up to set email alerts
|

Genome-wide and expression analysis of B-box gene family in pepper

Abstract: Background BBX transcription factors are a kind of zinc finger transcription factors with one or two B-box domains, which partilant in plant growth, development and response to abiotic or biotic stress. The BBX family has been identified in Arabidopsis, rice, tomato and some other model plant genomes. Results Here, 24 CaBBX genes were identified in pepper (Capsicum annuum L.), and the phylogenic analysis, structures, chromosomal location, gene expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
1
14
0
Order By: Relevance
“…The full-length amino acid sequences were used to construct a phylogenetic tree by the maximum likelihood (ML) method using IQ-TREE. As shown in Figure 1 a, the LbaBBX family was divided into five subgroups, consistent with previous studies of the gene family in tomato, pepper, and Arabidopsis [ 25 , 26 , 30 ]. We found that LbaBBX proteins assigned to the same group possess similar domain organizations.…”
Section: Resultssupporting
confidence: 86%
See 3 more Smart Citations
“…The full-length amino acid sequences were used to construct a phylogenetic tree by the maximum likelihood (ML) method using IQ-TREE. As shown in Figure 1 a, the LbaBBX family was divided into five subgroups, consistent with previous studies of the gene family in tomato, pepper, and Arabidopsis [ 25 , 26 , 30 ]. We found that LbaBBX proteins assigned to the same group possess similar domain organizations.…”
Section: Resultssupporting
confidence: 86%
“…The BBX gene family has recently been identified in many higher plants, such as Arabidopsis , tomato, and pepper [ 7 , 25 , 26 ]. The quantity of BBX genes varies among species.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, it is quite necessary to excavate more potential resistance genes and define their functional roles in the stress resistance of cucumber. BBXs have been identified and functionally characterized in many plants, where they are generally encoded by a multigene family, such as Arabidopsis thaliana [3], Oryza sativa [31], Solanum tuberosum [32], Malus domestica [33], Dendrobium officinale [34], Phyllostachys edulis [35], Vitis vinifera [36][37][38], and Capsicum annuum [39,40]. In addition, a recent study identified 26 cucumber BBX genes and found that some of them are associated with fruit development and carotenoid biosynthesis [41].…”
Section: Introductionmentioning
confidence: 99%